Advancements in Amorphous Oxides For Electrocatalytic Carbon Dioxide Reduction - Youcai Meng; Junyang Ding; Yifan Liu; Guangzhi Hu; Yanhong Feng; Yinghong Wu; Xijun Liu (Materials Today Catalysis)
Electrocatalytic CO2 reduction (ECR) is a crucial energy conversion technology that transforms CO2 into value-added chemicals, reducing reliance on fossil fuels and advancing energy transitions. Designing high-performance catalysts is pivotal for widespread adoption of CO2 reduction reactions, aiming for high activity, selectivity, and stability. Amorphous oxides represent a burgeoning frontier in this field, attracting attention due to their abundant active sites that refine the catalyst structure-performance relationship. This paper aims to provide an overview of recent advances in using amorphous oxides for ECR. We begin by introducing the basic theory of electrocatalytic CO2 reduction, followed by discussing current synthesis approaches for amorphous oxides in CO2 reduction, focusing on optimization strategies for these catalysts. Finally, we address challenges and future perspectives of amorphous oxides in ECR, aiming to foster the development of more efficient catalyst designs.